INFLUENCE OF DIETARY INCORPORATION OF MORINGA (MORINGA OLEIFERA) LEAF MEAL IN DIETS OF BROILER CHICKENS ON GROWTH PERFORMANCE AND ECONOMIC BENEFITS - Millam, Jacob Jafiya; Ishaya, A.; Midau, A.; Babale, M. D.; Abbaya, H. Y.; Ahmed, M. (FUDMA JOURNAL OF SCIENCES, 2024)
Consuming enough high-quality protein is essential for a long and healthy life. Because of their high-quality protein content, broiler chickens are a valuable food source that can support optimum growth and development and assist in address dietary deficiencies in Nigeria. The experiment was carried out at Adamawa State University Teaching and Research Farm, Mubi to evaluate the effects of diets containing varying levels of moringa (Moringa oleifera) leaf meal (MoLM) on growth performance and cost benefits fed to broiler chickens. The broiler chicks were purchased and maintained on a deep-litter system throughout the study. Fresh Moringa oleifera leaves were shed-dried and pulverised into fine particles. The powder was incorporated into the diets at 0, 0.5, 1, 1.5 and 2 g/kg denoted as control, 0.5MoLM, 1MoLM, 1.5MoLM and 2MoLM, respectively. The birds were randomly allotted to the different diets in a completely randomised design. Data collected during the study were: weight gain, feed intake, feed conversion ratio and the cost benefits of feeding MoLM-based diets. Significant (p
Keywords: broiler; chicken; moringa leaf meal; growth performance; cost-saving